Answer:
Step-by-step explanation:
m = 5 ; (3, -4)
y - y₁ = m (x - x₁)
y - [-4] = 5 (x - 3)
y + 4 = 5x - 15
y = 5x - 15 - 4
y = 5x - 19
A(n)=4+4(n-1)
a(n)=4+4n-4
a(n)=4n
76=4n
n=19
The sum of any arithmetic sequence (series are infinite) is:
(a+a(n))(n/2)
The average of the first and last terms times the number of terms, in this case we found that n=19 so:
19(4+76)/2=760
Answer:
.....
..
Step-by-step explanation:
umm.
ok free points if
Answer: I got -8/9. Hope this helps in any way shape of form.
Step-by-step explanation:
Answer:
I think the answer you have is correct
Step-by-step explanation: